2001
DOI: 10.1038/sj.mp.4000846
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and the tryptophan hydroxylase gene

Abstract: Tryptophan hydroxylase (TPH) is the rate-limiting enzyme of serotonin synthesis. In this casecontrol study, we investigated whether the TPH gene was a susceptibility factor for suicidal behavior. Seven polymorphisms spanning the entire gene were studied in a case-control study including 231 individuals who had attempted suicide and 281 controls. Significant associations were found between variants in introns 7, 8 and 9 ( 2 = 11.2, df = 1, P Ͻ 0.0008 for the allele distribution; these loci are in complete linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 24 publications
4
42
0
2
Order By: Relevance
“…TPH is the enzyme regulating the levels of serotonin in the brain, and the association between the TPH gene polymorphisms and suicide behavior has been investigated. After Nielsen et al (1994) and Mann et al (1997) reported the association between the TPH polymorphisms and suicide behavior, the TPH polymorphisms as A779C and A218C (Arango et al 2003), A6526G in the promoter region (Arango et al 2003), and 7 polymorphisms spanning the entire gene (Abbar et al 2001) have been studied concerning their relation with suicidal behavior though these polymorphisms did not involve replacement of amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…TPH is the enzyme regulating the levels of serotonin in the brain, and the association between the TPH gene polymorphisms and suicide behavior has been investigated. After Nielsen et al (1994) and Mann et al (1997) reported the association between the TPH polymorphisms and suicide behavior, the TPH polymorphisms as A779C and A218C (Arango et al 2003), A6526G in the promoter region (Arango et al 2003), and 7 polymorphisms spanning the entire gene (Abbar et al 2001) have been studied concerning their relation with suicidal behavior though these polymorphisms did not involve replacement of amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a polymorphism of putative functional significance in the human gene for aromatic L-amino acid decarboxylase (AADC), responsible for the conversion of 5-hydroxytryptophan to 5-HT, has been associated with bipolar disorder (Borglum et al, 1999). Finally, a frequent SNP in the human gene for tryptophan hydroxylase (TPH), the rate-limiting enzyme responsible for catalyzing the oxygenation of tryptophan to 5-hydroxytryptophan, has been associated with increased risk of suicide, impul-sivity, aggression, and alcoholism (Abbar et al, 2001;Manuck et al, 1999;New et al, 1998;Nielsen et al, 1994;Nielsen, Jenkins, Stefanisko, Jefferson, & Goldman, 1997;Nielsen et al, 1998;Nolan, Volavka, Lachman, & Saito, 2000). Recent work in TPH knockout mice has revealed the existence of a second TPH gene (TPH2), located on Chromosome 12, that is exclusively expressed in the murine brain and is responsible for regulating TPH expression and 5-HT synthesis in the murine central nervous system .…”
Section: Other Candidate 5-ht Synthesis Genesmentioning
confidence: 99%
“…Investigating seven polymorphisms spanning the entire gene in 231 individuals who attempted suicide, significant associations were found between violent suicide attempt and variants in introns 7, 8 and 9 (which are in complete linkage disequilibrium) and in the 3-non-coding region that encodes for the catalytic part of the enzyme. 50 Turecki et al 51 focused on polymorphisms in the promoter region (A-6526G and G-5806T) which were investigated together with the intron 7 A218C variant in 101 suicide completers from the French-Canadian population. In contrast to the fact that the single loci were not associated with suicide, a haplotype analysis revealed that one haplotype (À6526G À59061T 218C) was significantly more frequent among violent suicide victims than in normal controls (w 2 = 11.3, df = 2, P = 0.0008; OR = 2, CI:1.3-3.6).…”
Section: The Tph1 Genementioning
confidence: 99%